Sinergi Pendidikan, Pemasaran Digital dan UMKM sebagai Upaya dalam Mengembangkan Potensi Desa Rajamandala - Yugi Hilmi; Marni Marni; M Rifcky Adamsyah; Indri Lestari; Ace Abdul Kholik; Nurhalimah Nurhalimah (Universitas 45 Surabaya, 2025)
Community Service Program (KKN) is a form of student community service conducted directly in the village. The students' presence has a positive impact because they bring knowledge, ideas, and new breakthroughs that can help the village develop further. The KKN was conducted in Rajamandala Village, Rajapolah District, Tasikmalaya Regency. The program covered education and economics. The program was realized through educational activities, namely waste processing activities into works of art for students of Rajapolah 3 Elementary School. This educational activity provides benefits to encourage elementary school students to process waste into simple works of art. In addition, the economic sector includes workshops on digital marketing and finance for MSMEs in the village as an important step in MSME empowerment, small business development, and the introduction of online marketing strategies. These activities can certainly contribute to the development of the village itself, both in education, economics, and community empowerment as a whole.